Disruptions and civic education: How should young people be prepared for an uncertain future? : SpringerBriefs in Citizenship Education for the 21st Century. Singapore: Springer. DOI: https://doi.org/10.1007/978-981-96-5875-6 ISBN: 978-981-96-5875-6 - Afriani, Febi; Karo, Suratih Muhamad; Novemyanto, Alfin Dwi (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This book is the latest work by Kerry J. Kennedy, a leading scholar on civic education and global education policy. In this book, Kennedy presents a comprehensive analysis of how civic education needs to be reformulated amidst a rapidly changing and uncertain global landscape. Disruption, which is the key word in this discussion, does not merely refer to the development of digital technology, but to structural changes involving economic, political, social and environmental fields. Kennedy sees that the younger generation is living in the "century of disruption", a time when stability is no longer the norm, and uncertainty is inevitable. Therefore, this book proposes an educational approach that prepares learners to survive and participate meaningfully in this changing world.